Intimités amoureuses à l'ère du numérique Le cas des relations nouées dans les mondes sociaux en ligne - Cecchini, Amaranta (Editions Alphil Presses universitaires suisses, 2015)
The Internet and online social world have become the intermediaries of contemporary intimacy. Second Life offers exactly that, a 'second life', but in the virtual universe. This book delves into the use of this platform to understand the experiences of those who participate in a relationship there. How do communicational tools contribute to the organisation of intimate exchanges? What do these relationships reveal about the experiences of modern romantic liaisons? Drawing on the sociology of couples together with emotions and techniques, this research considers Second Life as both the developer and operator of contemporary intimacy. It addresses a subject at the centre of current affairs with an analysis of relational practises that remains little studied at present.